2019
DOI: 10.1002/app.47704
|View full text |Cite
|
Sign up to set email alerts
|

Chickpea flour‐based biofilms containing gallic acid to be used as active edible films

Abstract: Chickpea is an easily accessible nutritious legume. Besides, gallic acid is a widespread phenolic found in various plants. In this study, it is aimed to investigate the effects of pH (9 and 11), glycerol concentration (1 and 3% w/v of film solution) and gallic acid concentration (5 and 10% w/w of total solid) on color, opacity, mechanical strength, water vapor permeability (WVP), microstructure, chemical characteristic, antioxidant activity, and phenolic content of films. At pH 11, films are stronger, darker a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…In a previous water absorption kinetic study, water absorption of 30%–40% was observed for different cottonseed protein blends after 1000 min (~17 h) ( Yue et al., 2012 ). Nonetheless, no difference was observed (P > 0.05) for dissolved matter and moisture content, and the structural integrity of all the protein films was intact after removal of the films from water, as previously reported for other protein films ( Ramos et al., 2013 , Yue et al., 2012 , Kocakulak et al., 2019 ).…”
Section: Resultssupporting
confidence: 81%
“…In a previous water absorption kinetic study, water absorption of 30%–40% was observed for different cottonseed protein blends after 1000 min (~17 h) ( Yue et al., 2012 ). Nonetheless, no difference was observed (P > 0.05) for dissolved matter and moisture content, and the structural integrity of all the protein films was intact after removal of the films from water, as previously reported for other protein films ( Ramos et al., 2013 , Yue et al., 2012 , Kocakulak et al., 2019 ).…”
Section: Resultssupporting
confidence: 81%
“…A wide range of natural mixtures, such as pinha (Daudt et al., 2016), triticale (Borneo, Alba, & Aguirre, 2016), amaranth (Diéguez, Pelissari, do Amaral Sobral, & Menegalli, 2015), plantain (Gutiérrez, Guzmán, Medina, & Famá, 2016), defatted peanut flour (Riveros, Martin, Aguirre, & Grosso, 2017), and chickpea flour (Kocakulak, Sumnu, & Sahin, 2019) have been used to develop biodegradable films.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigations have demonstrated that chickpea flour is a good base material for films preparation (Díaz, Ferreiro, Rodríguez‐Otero, & Cobos, 2019; Kocakulak et al., 2019). The annual global production of chickpea grains ( Cicer arietinum L.) is 13.7 million metric tons per year (Wang, Beltranena, & Zijlstra, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the older literature considered many of these bioactive compounds as antinutritional factors in the diet as these interfered in the processes of digestion and absorption of nutrients. However, the tide has turned in their favor, with being recognized as health-promoting (2), groundnuts (3), lentils (4), soybeans (5), kidney beans (6), lima beans (7), pinto beans (8), adzuki beans (9), black beans (10), split beans (11), and green beans (12) and an overview of major bioactive compounds present in grain legume seeds bioactive components of foods [7]. Still, some of the antinutrients such as enzyme inhibitors can be easily removed by soaking legume seeds or by enough cooking while also softening them to enhance digestibility.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that phenolic content and protein content can be enhanced by legume incorporation. Kocakulak et al [9] reported that chickpeas seed flour can be used to make films having around 10% glycerol and had lower water vapor permeability than various flour-based ones. Additionally, the use of gallic acid, a phenolic acid, increased the flexibility of prepared film.…”
Section: Introductionmentioning
confidence: 99%